771 Sleep Health Knowledge, Attitudes, Beliefs, and Practices among Mothers with a History of Perinatal Depression or Anxiety. (3rd May 2021) - Hash, Jonika; Walker, Amy; Ward, Teresa; Spieker, Susan
Abstract: Introduction: Tailored interventions could optimize sleep health for mothers with a history of perinatal depression or anxiety. The purpose of this study was to describe sleep health knowledge, attitudes, beliefs, and practices among mothers who were previously treated for perinatal depression or anxiety, to inform future tailored sleep health interventions. Methods: Mothers (N = 16) who had previously received treatment for perinatal depression or anxiety from a clinic serving low-resourced communities completed a single-occasion research home visit that included a demographics questionnaire and semi-structured interview. Interview data were analyzed using inductive content analysis, adapted from grounded theory. Results: Mothers were, on average, 28.19 (SD = 7.71) years and had a child who was between 12 and 36 months. Of the mothers, 43.8% were White, 18.8% Black, 23.5% multiracial, 25.0% other race, 37.5% Hispanic, and 75.0% reported an annual household income of < 40, 000. "Needing to focus on sleep" was the core construct that emerged from the interview data, which was comprised of three domains. The first domain, "Having pretty good sleep, " described mothers' experiences of good sleep health including easily falling and staying asleep, feeling satisfied with their sleep, and feeling well-rested. The second domain, "Trying to get normal healthy sleep, " described mothers' experiences of poor sleep health and its consequences for physical and mental health. The third domain, "Wondering how to get better sleep with everything going on, " described everyday realities that got in the way of good sleep health including child sleep problems, competing demands on time, irregular work schedules, symptoms of depression or anxiety, and significant life transitions around school/work and pregnancy/postpartum. Conclusion: Findings showed a range of maternal sleep health experiences. Mothers' sleep health overlapped with mental health and wellbeing, children's sleep health, and social determinants of health. Future sleep health interventions for mothers with a history of perinatal depression or anxiety could include tailored approaches that build on existing maternal strengths, integrate with existing mental health care services and child sleep health interventions, address social determinants, and attend to significant life transitions. Support (if any): 2018 Sigma/Rosemary Berkel Crisp Award; NINR (T32NR016913); NICHD (R01HD080851, U54HD083091).